New species of Glossoscolex and Fimoscolex earthworms (Oligochaeta: Glossoscolecidae) from Embrapa Forestry, Paraná, Brazil - M., Alexander Feijoo; Brown, George G. (Zootaxa, 2018)
Three new earthworm species in two genera of the Glossoscolecidae family, common in Southern and Southeastern Brazil, collected in the highland plateaus of Paraná, are described: Glossoscolex (Glossoscolex) maschio sp. nov. and Glossoscolex (Glossoscolex) embrapaensis sp. nov., and Fimoscolex nivae sp. nov. G. embrapaensis is a small, unpigmented endogeic belonging to the truncatus species group, having male pore on segment 17, while G. maschio is a large, pigmented epiendogeic species belonging to the giganteus species group, having male pore on segment 19. F. nivae is a very slender, small unpigmented endogeic species. All specimens were collected in native Araucaria forest on the grounds of Embrapa Forestry, but G. maschio was found exclusively associated with native forest, while G. embrapaensis and F. nivae were also collected in Eucalyptus, Pinus or Araucaria plantations, native grassland or fallow land, indicating their resistance to soil disturbance and land use change.